New type of fluxgate magnetometer for the heart’s magnetic fields detection - Rybalko Ruslan; Haueisen Jens; Hofmann Christian (Current Directions in Biomedical Engineering, 2015)
The application area of fluxgate sensors is limited by their sensitivity. Medical researches create high demand on the magnetometers with the characteristics of high accuracy and sensibility for measuring weak magnetic fields produced by the human body, such as the heart‘s magnetic field. Due to the insufficient sensitivity of fluxgate sensors, superconducting magnetometers (SQUID) take the dominant position for the cardiomagnetic measurements. They have to be cooled by liquefied gases and it leads to high service costs. Therefore an idea of creating a high sensitive sensor based on fluxgate principles and known methods of measurement is attractive and up to date. This paper is dedicated to the modified flux-gate sensors based on Racetrack technology with a new approach of signal demodulation. The improved fluxgate sensor system provides detection of the heart‘s magnetic field without additional expenditures for use.